Effect of Diabetes Mellitus on Tuberculosis Treatment Outcomes among Tuberculosis Patients in Kelantan, Malaysia - Siti Rohana AHMAD; Nor Azwany YAACOB; Mat Zuki JAEB; Zalmizy HUSSIN; Wan Mohd Zahiruddin WAN MOHAMMAD (Tehran University of Medical Sciences, 2020)
Background: There is growing evidence that DM may play an important role in the occurrence of unsuccessful TB treatment outcomes. This study was undertaken to examine the prevalence of  DM among TB population, compare the profile of TB patients with and without DM and determine the effect of DM on unsuccessful treatment outcomes among TB patients in Kelantan state, Malaysia from 2012 to 2016. Methods: A cross sectional study was conducted in Sep 2017 using data from registered TB cases in Kelantan state, Malaysia from 2012 to 2016. The profile of TB patients with and without DM were compared in univariable analysis. Multiple logistic regression was used to determine association between DM and unsuccessful treatment outcomes. Results: A total of 1854 TB patients were diagnosed with DM. The annual proportion was ranging from 26 to 29%. TB patients with DM had an older age, live single, low educational status, poor chest x ray finding and diagnosed with smear positive sputum compared to TB patients without DM. TB patients with DM had three times higher risk to develop unsuccessful TB treatment outcomes compared to TB patients without DM (95% CI 2.47-3.58; P = 0.012) in multivariable analysis. Conclusion: Those with DM had the worst prognosis of TB outcomes among the significant risk factors. TB control program in Malaysia will need to expand efforts to focus on treatment of TB-DM patients to improve their cure rates in order to achieve the goals of tuberculosis elimination.